2023
DOI: 10.1002/cam4.6351
|View full text |Cite
|
Sign up to set email alerts
|

The many “costs” of transportation: Examining what cancer caregivers experience as transportation obstacles

Abstract: BackgroundTransportation has been identified as a specific source of burden for cancer caregivers. This study examined cancer caregivers' subjective experiences and objectives costs associated with transportation over a 6‐month period of providing end‐of‐life care to a family member or friend.MethodsThis was a multi‐site longitudinal, prospective cohort study that followed 223 caregiver–patient dyads. Data were collected using biweekly, semi‐structured interviews for up to 6 months and collection of all caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous analyses revealed that biweekly transportation costs can be as high as $43.60, and almost 60% of those surveyed reported a need for transportation accommodations on the "institutional level". 11 The results of this study emphasize a need for caretaker support and interventions. Previous research indicates promising results with regard to intervention efficacy; for instance, interventions that involve both caretakers and the patient-caretaker dyads yielded statistically significant improvements in the same core characteristics described in the present study: mental well-being, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 74%
“…Previous analyses revealed that biweekly transportation costs can be as high as $43.60, and almost 60% of those surveyed reported a need for transportation accommodations on the "institutional level". 11 The results of this study emphasize a need for caretaker support and interventions. Previous research indicates promising results with regard to intervention efficacy; for instance, interventions that involve both caretakers and the patient-caretaker dyads yielded statistically significant improvements in the same core characteristics described in the present study: mental well-being, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 74%